2017
DOI: 10.1016/j.virol.2017.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Human norovirus inhibition by a human milk oligosaccharide

Abstract: Human noroviruses are the leading cause of outbreaks of acute gastroenteritis. Norovirus interactions with histo-blood group antigens (HBGAs) are known to be important for an infection. In this study, we identified the HBGA binding pocket for an emerging GII genotype 17 (GII.17) variant using X-ray crystallography. The GII.17 variant bound the HBGA with an equivalent set of residues as the leading pandemic GII.4 variants. These structural data highlights the conserved nature of HBGA binding site between preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
121
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 125 publications
(127 citation statements)
references
References 55 publications
6
121
0
Order By: Relevance
“…In the GII noroviruses, the coordination occurs at a dimeric interface of the P domain dimer and involves residues from both monomers (Figure A). In both the pandemic GII.4 and rapidly evolving GII.17 strains, the HBGA binding pocket is remarkably similar and accounts for various HBGA types ( Table ) …”
Section: Role Of Glycans In the Viral Attachmentmentioning
confidence: 99%
See 4 more Smart Citations
“…In the GII noroviruses, the coordination occurs at a dimeric interface of the P domain dimer and involves residues from both monomers (Figure A). In both the pandemic GII.4 and rapidly evolving GII.17 strains, the HBGA binding pocket is remarkably similar and accounts for various HBGA types ( Table ) …”
Section: Role Of Glycans In the Viral Attachmentmentioning
confidence: 99%
“…This can be utilized by HMOs, structurally similar to HBGA epitopes to provide antiviral protection. Indeed, structural analysis revealed that 2′FL occupied the HBGAs’ binding pocket of GII.10 and the emerging GII.17 norovirus strain in a manner that was essentially identical to HBGAs. The coordination of 2′FL was also preserved among three complexes (Figure B and C).…”
Section: Role Of Glycans In the Viral Attachmentmentioning
confidence: 99%
See 3 more Smart Citations